Awareness of flood victims in the East-Coast region of Malaysia towards the takaful flood policy: a crosstabulation analysis based on demographic variables - Che Mohd Salleh, Marhanum; Megat Laksana, Nan Noorhidayu (Accounting Research Institute (ARI), 2018)
This study was conducted to; first, investigate the level of awareness among flood victims in Malaysia towards the takaful policy. Second, to examine differences of demographic background (age, marital status, occupation, education background, and income level) among the victims towards awareness on the takaful. Overall, a total of 536 flood victims located at the east-coast area of Malaysia participated in the survey. Based on the descriptive and crosstabulation analyses, most of the victims were uncertain about the takaful. In terms of background differences, the younger generation were more aware compared to the elders, single victims were more aware than the married, and those with a high level of education (diploma, degree, and PhD holders) were more aware of the existence of takaful and the need to have takaful protection. The findings of this study provide important suggestion to offer an affordable micro-takaful policy for future financial protection for the lower income and most vulnerable flood victims in the country. Various efforts should be done to increase the level of awareness among Malaysians on the importance of participating in the takaful policy.